The ‘corporate cultural system’: examining the twenty-first century business practice of constructing and managing meaning - Montgomery, MS (2022)
This thesis brings the fields of Business Studies and Religious Studies into dialogue to examine the contemporary corporate practice of the manufacturing and management of ‘meaning.’ In particular, it explores how the practitioners, academics, and consultants who make up the business community conceptualize companies’ meaning-making activity. What do they consider corporate ‘meaning’ to be, how do they understand the work to construct it, and what ends do they believe it can support?